Liposomes or extracellular vesicles : A comprehensive comparison of both lipid bilayer vesicles for pulmonary drug delivery - Al-Jipouri, Ali; Almurisi, Samah Hamed; AL-japairai, Khater Ahmed Saeed; Latifah Munirah, Bakar; Doolaanea, Abd Almonem (MDPI, 2023)
The rapid and non-invasive pulmonary drug delivery (PDD) has attracted great attention compared to the other routes. However, nanoparticle platforms, like liposomes (LPs) and extracellular vesicles (EVs), require extensive reformulation to suit the requirements of PDD. LPs are artificial vesicles composed of lipid bilayers capable of encapsulating hydrophilic and hydrophobic substances, whereas EVs are natural vesicles secreted by cells. Additionally, novel LPs-EVs hybrid vesicles may confer the best of both. The preparation methods of EVs are distinguished from LPs since they rely mainly on extraction and purification, whereas the LPs are synthesized from their basic ingredients. Similarly, drug loading methods into/onto EVs are distinguished whereby they are cell- or non-cell-based, whereas LPs are loaded via passive or active approaches. This review discusses the progress in LPs and EVs as well as hybrid vesicles with a special focus on PDD. It also provides a perspective comparison between LPs and EVs from various aspects (composition, preparation/extraction, drug loading, and large-scale manufacturing) as well as the future prospects for inhaled therapeutics. In addition, it discusses the challenges that may be encountered in scaling up the production and presents our view regarding the clinical translation of the laboratory findings into commercial products.